ANALISIS LAPORAN KEUANGAN UNTUK MENILAI KINERJA KEUANGAN PADA PT. ASTRA INTERNASIONAL,Tbk. PERIODE 2016-2020 - JAMALUDIN JAMALUDIN (Universitas Kuningan, 2023)
AbstractThe health of a bank can be interpreted as the ability of a bank to carry out normal banking operations and be able to fulfill all of its obligations properly in ways that comply with applicable banking regulations. The purpose of this research is to analyze the financial performance at PT. Astra International, Tbk Period 2016-2020. The research method used in this study is a quantitative method, the data used is secondary data, the population in this study is all financial reports at PT. Astra International, Tbk. The sample used in this study is the financial statements of PT. Astra International, Tbk for the 2016-2020 period, in the form of a balance sheet and profit and loss report. The result of this research is the Liquidity Ratio. From the liquidity ratio, PT Astra Tbk is not yet liquid or unable to meet its financial short-term obligations when billed. Profitability Ratio. The average calculation of 24.2% with the industry standard is 30%, so the condition of financial performance is not good because it is below the company's industry standard. Solvency Ratio. The company's industry standard is 90%, so the financial performance is in a